(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In the article, simple and complex reflexes are included in a number of innate reflexes transmitted from generation to generation in bees. in the complex behavior of bees, it is necessary to distinguish between such basic concepts as reflex and instinct. provides information about the reflex - the reaction of the body to external influences and the presence of two types of reflexes - unconditional and conditional - in the animal world, including bees.